2020
DOI: 10.1111/rec.13209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seed storing duration and sowing year on the seedling establishment of grassland species in xeric environments

Abstract: Theavailability of seeds of native species in many countries for grassland restoration is limited; therefore, ex situ seed banks can gain importance as a source of germplasm in the future. We tested the usability of seed accessions of the Pannon Seed Bank for reintroduction with the aim to restore sandy grassland in Hungary. Seeds of 10 native sandy grassland species were seeded in the year of collection and after one or two years of storage. The establishment was estimated by counting seedlings along seeded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Sown species established best in gaps as a result of low weed abundance, and began to expand into surrounding non‐gap areas within 5 years, illustrating the potential of localized disturbances for broader‐scale restoration. Kövendi‐Jakó et al (2021) also showed the importance of seed sowing for re‐establishment of sandy grasslands in Hungary. They found, however, that establishment varied among years and argued that repeated seeding could be advantageous under stressful conditions.…”
Section: Limiting Factors and Novel Measures Of Restoration Successmentioning
confidence: 98%
“…Sown species established best in gaps as a result of low weed abundance, and began to expand into surrounding non‐gap areas within 5 years, illustrating the potential of localized disturbances for broader‐scale restoration. Kövendi‐Jakó et al (2021) also showed the importance of seed sowing for re‐establishment of sandy grasslands in Hungary. They found, however, that establishment varied among years and argued that repeated seeding could be advantageous under stressful conditions.…”
Section: Limiting Factors and Novel Measures Of Restoration Successmentioning
confidence: 98%
“…One reason for this may be that under eld conditions a high intraspeci c competition was present between the individuals of species with high germination rate and negative frequency-dependence resulted in a decreased survival rate of individuals [50] . Another reason can be that in the eld unfavourable post-germination conditions resulted in high mortality of seedlings, so the establishment of species with lower germination rate and gradual emergence may have been more successful [42,51,52] .…”
Section: Discussionmentioning
confidence: 99%
“…One reason for this may be that under field conditions a high intraspecific competition was present between the individuals of species with high germination rate and negative frequency-dependence resulted in a decreased survival rate of individuals 52 . Another reason can be that in the field unfavourable post-germination conditions resulted in high mortality of seedlings, so the establishment of species with lower germination rate and gradual emergence may have been more successful 42,53,54 .…”
Section: Discussionmentioning
confidence: 99%